Fetal isovolumetric time intervals as a marker of abnormal cardiac function in fetal anemia from homozygous alpha thalassemia‐1 disease. (11th September 2017) - Tongprasert, Fuanglada; Srisupundit, Kasemsri; Luewan, Suchaya; Traisrisilp, Kuntharee; Jatavan, Phudit; Tongsong, Theera
Abstract: Objective: To determine whether fetal isovolumetric time intervals can be an early sonographic marker of fetal anemia in fetuses with homozygous alpha thalassemia‐1. Methods: Pregnancies at risk for fetal homozygous alpha thalassemia‐1 disease at 18–22 weeks were recruited before cordocentesis for hemoglobin typing. Isovolumetric contraction time (ICT) and isovolumetric relaxation time (IRT) intervals were measured by placing pulsed wave Doppler sample volume within the left ventricle to obtain the mitral and aortic waveform. Time intervals were compared between the affected group of homozygous alpha thalassemia‐1 fetuses and the unaffected group. Results: Among 70 fetuses at risk, 28 cases were diagnosed as affected by homozygous alpha thalassemia‐1 disease. Mean ICT and ICT + IRT intervals in the affected group were significantly longer than in the unaffected group (47.9 ± 12.5 ms vs 35.0 ± 6.7 ms, p  < 0.001; and 96.2 ± 13.6 ms vs 80.9 ± 10.6 ms, p  < 0.001. ICT effectively predicted affected fetuses with 71.4% sensitivity and 78.6% specificity using a cutoff value ≥40 ms. Conclusions: Isovolumetric contraction time was significantly prolonged in fetal anemia from homozygous alpha thalassemia‐1 during the early stage of hydropic changes. Because of its simple measurement and high efficacy, ICT can be a useful marker for prenatal screening of abnormal cardiac function in fetal anemia. © 2017 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? The increased myocardial performance index in ventricular dysfunction results from a prolongation of the isovolumetric time intervals (isovolumetric contraction time and isovolumetric relaxation time) with unchanged ejection time. What does this study add? At 18–22 weeks of gestation, the selective measurement of ICT is a better marker as compared with myocardial performance index for fetal cardiac function monitoring in the hypervolemic heart secondary to anemia caused by homozygous alpha thalassemia‐1.